BioWinfordMR: an online platform for comprehensive Mendelian randomization analysis - Wang, Yunfeng; Wu, Tong; Lu, Xinliang; Wang, Xiaoqiong; Xue, Wenhua (Frontiers in Immunology, 2026)
BackgroundMendelian randomization (MR) has become a tool for the rapid and accurate identification of genetic relationships between phenotypes. However, owing to the lack of rigorous and standard analytical tools, many MR conclusions are unreproducible or controversial. Therefore, we developed the BioWinfordMR platform, which integrates curated GWAS data from multiple categories using a Shiny server to automate MR analysis.MethodWe developed an online platform, BioWinfordMR, to infer the causality between sepsis, gut microbiota, and immune cells. BioWinfordMR efficiently integrates core analytical functions for MR studies. Its scientific and rigorous analytical pipeline coupled with high-performance computing capabilities from large-scale servers ensures reproducible and valid analytical conclusions. The main findings of the case study were verified using flow cytometry and real-time polymerase chain reaction (RT-PCR) analysis.ResultsThrough systematic analysis, we found that CD62L-CD86+ myeloid dendritic cells (DCs) were key intermediate factors that increased the risk of sepsis with enhanced gut microbiota. We also identified two risk genes, ENTPD5 and MANEA, which are associated with sepsis.ConclusionsWe developed a platform called BioWinfordMR to facilitate various MR analyses. BioWinfordMR ensures the accuracy and reproducibility of MR analysis and allows the discovery of potential causal relationships.